Analyzing the spatial distribution of manufacturing clusters in the Istanbul Metropolitan Area - Ferhan Gezici; Burcu Muderrisoglu (European Regional Science Association (ERSA), 2010)
While the location and concentration of industrial activities has been a significant topic for both urban planners and urban and regional economist, the cluster approach has contributed to theory and empirical works by emphasizing the significancy of networks with respect to the competitiveness. According to the economic literature; clusters are the geographical concentration of firms with the other connected institutions. The presence of the complementary actors in the cluster, is the point which raises the connectivity of firms. Porter claims that the competitiveness of a region is based on the competitiveness of the industries, which have a deep network. Thus, according to the current cluster policy, the target group has shifted away from horizontal sectors to wider "value chains". Therefore, the studies which are trying to understand both their location decisions and relations to the other firms and institutions would make contributions to the literature of economic geography. This paper focuses on the location decisions of industry clusters in Istanbul Metropolitan Area. The main questions of the paper are; "what are the factors that form the location decisions?", "are there any sectoral differences which effect these decisions?, and "do the clusters have different characteristics due to their location in the city as central or peripheral ones?". In the analysis of Istanbul, 42 clusters in 14 districts and in 10 sub sectors are determined. The firm structures and the densities of the clusters differ according to their spatial distribution as well as their relations with different actors. These differences and effects on the location decisions are evaluated in Istanbul Metropolitan Area.
Keywords: 330; manufacturing industry; agglomeration; cluster; spatial distribution; Istanbul Metropolitan Area